FUEL CONSUMPTION OF A SPARK IGNITION ENGINE BLENDED WITH MTBE - Al-Farayedhi, Abdulghani A. (2020)
Gasoline engines are widely used in automotive applications and power generation. In these engines, the combustion of converting the fuel energy into mechanical work through combustion takes place rapidly in cycles. An important parameter used as an indicator to the efficiency of engines is the brake specific fuel consumption (bsfc). The equivalence ratio has an appreciable effect on the engine performance. This paper studies experimentally the effects of using an oxygenate namely methyl teriary butyl eyher (MTBE) on bsfc of a typical spark ignition engine. MTBE, which was blended with unleaded fuel in three ratios, was investigated. The engine sfc was measured at a variety of engine operating conditions using an engine dynamometer set-up. This paper presents the comparison of bsfc between the fuel blended with MTBE and the unleaded fuel. The results are presented in terms of equivalence ratio and their effects are discussed in this paper.